Application of the repertory grid technique for evaluation of the quality of the educational service - N. Bugro (Цифровая трансформация)
This article discusses the use of G.Kelly’s technique of the repertory grid for the task of evaluating the quality of educational services. This technique allows to develop of interviewing technique that promotes a deeper analysis of the characteristics of the educational services, and to receive more complete and accurate information from respondents. On the basis of the received data the various methods are offered for the visualization: charts and graphs, cluster analysis, factor analysis.